Analysis of optical properties and mechanism of photoluminescence enhancement of quantum dot - ferroelectric liquid crystal composite - Vimal, Tripti; Singh, Dharmendra Pratap; Agrahari, Kaushlendra; Srivastava, Atul; Manohar, Rajiv (Photonics Letters of Poland, 2016)
ZnS QDs (Quantum Dots) were dispersed in FLC mixture (SCE4). The dispersion of QDs in FLC causes enhanced Photoluminescence that can be attributed to the high molecular orderning of the composite system induced by QDs. FWHM (full width half maxima) values of peaks reveals that the presence of QDs in FLC material faours the NB (near band) emissions. The POM (Polarizing Optical Microscope) images confirms the change in the alignment of FLC molecules after the dispersion of QDs. Full Text: PDF References S.W. Lee, C. Mao, C.E. Flynn, A.M. Belcher, "Ordering of Quantum Dots Using Genetically Engineered Viruses", Science 3, 892 (2002). CrossRef M. Tamborra, M. Striccoli, R. Comparelli, M.L. Curri, A. Petrella, A. Agostiano, "Optical properties of hybrid composites based on highly luminescent CdS nanocrystals in polymer", Nanotechn. 15(4), S240 (2004). CrossRef E. Kikuchi, S. Kitada, A. Ohno, S. Aramaki, S. Maenosono, "Solution-processed polymer-free photovoltaic devices consisting of PbSe colloidal quantum dots and tetrabenzoporphyrins", Appl. Phys. Lett. 92, 173307 (2008). CrossRef T. Joshi, A. Kumar, J. Prakash, A.M. Biradar, "Low power operation of ferroelectric liquid crystal system dispersed with zinc oxide nanoparticles", Appl. Phys. Lett. 96, 253109 (2010). CrossRef S. K. Gupta, D.P. Singh, P.K. Tripathi, R. Manohar, M. Varia, L.K. Sagar, S. Kumar, "CdSe quantum dot-dispersed DOBAMBC: an electro-optical study", Liq. Cryst. 40, 528 (2013). CrossRef A.K. Kole, C.S. Tiwary, P. Kumbhakar, "Room temperature synthesis of Mn2+ doped ZnS d-dots and observation of tunable dual emission: Effects of doping concentration, temperature, and ultraviolet light illumination", J. Appl. Phys. 113, 114308 (2013). CrossRef H. Qi, T. Hegmann, "Multiple Alignment Modes for Nematic Liquid Crystals Doped with Alkylthiol-Capped Gold Nanoparticles", ACS Appl. Mater. Interfaces 1, 1731 (2009). CrossRef E. Mohagheghpour, M. Rabiee, F. Moztarzadeh, M. Tahriri, "Effect of manganese (Mn) doping on the optical properties of zinc sulfide (ZnS) semiconductor nanocrystals", J. Ceramic Proc. Research 11(2), 144 (2010). DirectLink P. Goel, M. Arora, "Mechanism of photoluminescence enhancement and quenching in Nd2O3 nanoparticles?ferroelectric liquid crystal nanocomposites", RSC Adv. 5, 14974 (2015). CrossRef I.A. Ostapenko, G. Honig, C. Kindel, S. Rodt, A.Strittmatter, A. Hoffmann, D. Bimberg, "Large internal dipole moment in InGaN/GaN quantum dots", Appl. Phys. Lett. 97, 063103 (2010). CrossRef A. Kumar, J. Prakash, A.D. Deshmukh, D. Haranath, P. Silotia, A.M. Biradar, "Enhancing the photoluminescence of ferroelectric liquid crystal by doping with ZnS quantum dots", Appl. Phys. Lett. 100, 134101 (2012). CrossRef A. Kumar, S. Tripathi, A.D. Deshmukh, D. Haranath, P. Singh, A.M. Biradar, "Time evolution photoluminescence studies of quantum dot doped ferroelectric liquid crystals", J. Phys. D: Appl. Phys. 46, 195302 (2013). CrossRef D.P. Singh, S.K. Gupta, A. Srivastava, R. Manohar, "The phenomenon of induced photoluminescence in ferroelectric mesophase", J. Luminescence 139, 60 (2013). CrossRef O. Lupan, S. Shishiyanu, V. Ursaki, H. Khallaf, L. Chow et al., "Synthesis of nanostructured Al-doped zinc oxide films on Si for solar cells applications", Solar Energy Materials & Solar Cells 93, 1417 (2009). CrossRef W.K. Bae, M.K. Nam, K. Char, S. Lee, "Gram-Scale One-Pot Synthesis of Highly Luminescent Blue Emitting Cd1?xZnxS/ZnS Nanocrystals", Chem. Mater. 20, 5307 (2008). CrossRef